Synthesis of Fe3O4@m-SiO2 Nanocomposites Using Rice Husk Ash Derived SiO2 - Nazli Aharipour; Adrine Malek khachatourian; Ali Nemati (Iranian Journal of Materials Science and Engineering)
Fe3O4 nanoparticles (NPs) with a continuous and mesoporous silica (m-SiO2) shell were synthesized using a one-step method, sourcing silica from rice husk ash (RHA). The rice husk was thermally treated to obtain ash, from which silica was extracted as sodium silicate and precipitated by pH reduction. This silica powder, combined with iron chloride salts, facilitated the synthesis of the core-shell NPs. Mint extract acted as a capping agent to prevent agglomeration, and CTAB (cetyltrimethylammonium bromide) was used to create the porous SiO2 shell. X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), and transmission electron microscopy (TEM) characterization investigated the structure, size, and shell formation. Coating integrity and suspension stability were assessed through Fourier transform infrared spectroscopy (FTIR) and dynamic light scattering (DLS). DLS analysis showed a relatively narrow particle size distribution with an average hydrodynamic size of 72.6 nm. Small-angle X-ray scattering (SAXS) provided insights into the meso- and nanoscale structure, while BET and nitrogen adsorption-desorption isotherms confirmed the mesoporous nature of the silica shell. Magnetization measurements showed superparamagnetic behavior, with specific magnetization values of 57.9 emu/g for Fe3O4 and 27.5 emu/g for Fe3O4@m-SiO2. These results confirm the successful synthesis of superparamagnetic magnetite NPs with a mesoporous silica coating from RHA.